Phytocannabinoids and migraine: An integrative review - Bechara, Gabriela Ilias; Esposito, Sandro Blasi (Seven Editora, 2023)
The latest years have shown a relationship between the famous endocannabinoid system and pain processing, bringing the possibility of its exogenous form, phytocannabinoids, for treatment of epilepsy, neuropathic pain, and now migraine. This review seeks to evaluate the present literature and analyze the possibility of phytocannabinoids in migraine treatment. Based on the literature of the latest 20 years, the research terms were: "endocannabinoids and migrânea", "phytocannabinoids and migrânea" and "migrânea juvenile and cannabidiol", with 128 results total, of which only 19 have fitted the criteria for analysis. Though is a very pertinent theme, there is no literature enough for clinical analysis of the use of phytocannabinoid in migraine, even when the results in an animal model and reviews have shown a positive effect, it is not possible to speculate the dose, safety, and efficacy in clinical use for now. More randomized human trials are necessary. DOI:https://doi.org/10.56238/devopinterscie-235